PE teachers' perspectives on the concept of a festival of sports and the value in secondary pupil's educational experience generated from the collaboration between sport tours operators and the PE teachers - Nguyen, Anh Quan (2014)
In recent years, the emerging market of sport tourism has become one of the most popular among all tourism sectors. This dissertation focuses on PE teachers' perspectives on the concept of a festival of sports and the value in secondary pupil's educational experience generated from the collaboration between sport tours operators and the PE teachers. The information for data analysis consists of interviews with Rayburn Sports Tours' staffs and also PE teachers from various secondary schools in the United Kingdom. The interviews with Rayburn Sports Tours reveal several possible changes in the expectation of PE teachers about a sports tour and their value creation in the form of experiences. Additionally, the interviews with the PE teachers unfold the factors that might influence them to recommend "Festival of Sports" to their secondary pupils and the triggers as well as the barriers in making them become ambassadors. Moreover, the value co-creation between Rayburn Sports Tours and PE teachers, how value is created from such collaboration and how it contributes to better educational experiences for secondary pupils are also explored. This dissertation also discusses some managerial implications for Rayburn Sports Tours as well as its limitations and makes suggestions for further study.